2011
DOI: 10.1002/jcb.23349
|View full text |Cite
|
Sign up to set email alerts
|

CD109‐mediated degradation of TGF‐β receptors and inhibition of TGF‐β responses involve regulation of SMAD7 and Smurf2 localization and function

Abstract: Transforming growth factor-β (TGF-β) is a multifunctional cytokine that regulates a wide variety of cellular processes including proliferation, differentiation, and extracellular matrix deposition. Dysregulation of TGF-β signaling is associated with several diseases such as cancer and tissue fibrosis. TGF-β signals through two transmembrane proteins known as the type I (TGFBR1) and type II (TGFBR2) receptors. The levels of these receptors at the cell surface are tightly regulated by several mechanisms, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 29 publications
5
61
1
Order By: Relevance
“…c High anti-CD109 staining in the TNBC tumors (magnification ×400) signaling [13]. In addition, CD109 promotes localization of the TGF-β receptors into the caveolar compartment in the presence of ligand and facilitates TGF-β-receptor degradation [14]. Thus, CD109 regulates TGF-β receptor endocytosis and degradation to inhibit TGF-β signaling.…”
Section: Discussionmentioning
confidence: 94%
“…c High anti-CD109 staining in the TNBC tumors (magnification ×400) signaling [13]. In addition, CD109 promotes localization of the TGF-β receptors into the caveolar compartment in the presence of ligand and facilitates TGF-β-receptor degradation [14]. Thus, CD109 regulates TGF-β receptor endocytosis and degradation to inhibit TGF-β signaling.…”
Section: Discussionmentioning
confidence: 94%
“…Soluble CD109 can bind to all 3 isoforms of TGFβ-1/2/3, thus interfering with the activation of TGFβ dependent signaling34. In fact, membrane bound CD109 acts as a co-receptor for TGFβ1 and results in internalization and degradation of TGFβ receptors via binding to Smad73536. Further, CILP inhibits transcriptional activation of matrix genes in NP cells by binding to TGFβ1 and inhibiting the downstream phosphorylation of Smads, thereby promoting disc degeneration37.…”
Section: Discussionmentioning
confidence: 99%
“…CD109 promotes TGF-b receptor internalization and degradation by regulation of SMAD7 and SMURF2 activity in ubiquitin-mediated proteolysis [14,15]. It was also reported that proteolytic processing of CD109 by furin or mesotrypsin is required for its function in cultured cells [16,17].…”
Section: Introductionmentioning
confidence: 92%